EKSPLORASI STRATEGI GURU DALAM IMPLEMENTASI PROGRAM ANTI BULLYING DI SDN TENGGULUNAN CANDI SIDOARJO - Kurniawati, Yuli; Tirtoni, Feri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Bullying is a problem that is still often encountered in the elementary school environment and has a negative impact on the social, emotional, and learning comfort of students. After face-to-face learning after the COVID-19 pandemic, SDN Tenggulunan Candi Sidoarjo experienced changes in student behavior, such as increased mockery of each other, low empathy, and the formation of closed friend groups that have the potential to trigger bullying. This research aims to explore various strategies carried out by teachers in implementing anti-bullying programs and their influence on the creation of a school climate. This study applies a descriptive qualitative approach with a case study method. The subjects involved in this study consist of teachers, students, and the Anti-Bullying Task Force Team. Data collection was carried out through interviews, observations, and documentation review. Meanwhile, the data analysis uses the Miles and Huberman interactive model combined with triangulation techniques to ensure the validity of the data. The results of the study showed that teachers applied preventive and curative strategies through habituation of positive behavior, instilling character values, implementing class rules, 6S culture, empowering the Anti-Bullying Task Force Team, and handling cases in an educational and collaborative manner with parents. The implementation of this strategy has an impact on decreasing bullying behavior, increasing student empathy and tolerance, and creating a safe, comfortable, and supportive school environment.